2023
DOI: 10.1088/1741-2552/accece
|View full text |Cite
|
Sign up to set email alerts
|

Firing-rate-modulated spike detection and neural decoding co-design

Abstract: Objective: Translational efforts on spike-signal-based implantable brain-machine interfaces (BMIs) are increasingly aiming to minimise bandwidth while maintaining decoding performance. Developing these BMIs requires advances in neuroscience and electronic technology, as well as using low-complexity spike detection algorithms and high-performance machine learning models. While some state-of-the-art BMI systems jointly design spike detection algorithms and machine learning models, it remains unclear how the dete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Intracortical BCI correlation coding can be inspired by the correlation coding model of neuronal firing ( Panzeri et al, 1999 ). This model suggests that correlations between action potentials or “spikes” within a spike sequence may carry additional information beyond the simple timing of the spikes ( Ahmadi et al, 2021 ; Zhang and Constandinou, 2023 ). Correlations may also carry information that is not present in the average firing rate of the two pairs of neurons ( Decharms and Merzenich, 1996 ).…”
Section: Definition and Mechanisms Models Of Bci Neural Codingmentioning
confidence: 99%
See 2 more Smart Citations
“…Intracortical BCI correlation coding can be inspired by the correlation coding model of neuronal firing ( Panzeri et al, 1999 ). This model suggests that correlations between action potentials or “spikes” within a spike sequence may carry additional information beyond the simple timing of the spikes ( Ahmadi et al, 2021 ; Zhang and Constandinou, 2023 ). Correlations may also carry information that is not present in the average firing rate of the two pairs of neurons ( Decharms and Merzenich, 1996 ).…”
Section: Definition and Mechanisms Models Of Bci Neural Codingmentioning
confidence: 99%
“…To date, most LFP-based BCI research has been carried out based on typical center-out arm movements ( Rickert et al, 2005 ; Heldman et al, 2006 ; Wang, 2006 ), and some studies have employed point-to-point motor tasks ( Ahmadi et al, 2021 ; Zhang and Constandinou, 2023 ). It has been shown that the M1 tune encodes movement direction ( Georgopoulos et al, 1986 ) and velocity.…”
Section: Existing Main Bci Paradigms and Neural Codingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the performance of iBMI systems employing such compression with increasing electrode count on the neural interface array is still unknown. Some other works such as [27], [28] advocate the integration of decoders in the implant (as shown in Fig. 1(b) Scheme-I/II followed by Scheme-D).…”
Section: Activity Dependent Processingmentioning
confidence: 99%